A narrative review of the methodologies used in the study of nocturnal turbulence within and above the Amazon rainforest obtained through the Amazon Tall Tower Observatory experimental site (Research, Society and Development, 2021)
This paper aims to document which methodologies are used in the studies of intermittent turbulent events of variable intensity and periodicity, which provide an episodic connection between the canopy and the atmosphere and can induce oscillatory behavior in the nocturnal boundary layer carried out specifically at the Amazon Tall experimental site Tower Observatory (ATTO) through a narrative literature review of the main articles published during the period 2012 to 2021. A literature search was carried out in the ATTO project database, where this database has all peer-reviewed publications in journals made in this project between 2012 to 2021. All articles were reviewed, so from 81 publications in total only 3 articles are categorized as studies on intermittent turbulent events in the nocturnal boundary layer. From this, a synthesis of the methodologies used in these 3 articles was made. It is concluded that data were obtained from direct measurements in the towers: wind direction and speed, air temperature, net radiation, precipitation, soil moisture, CO, CO2, O3, CH4 and CN fluxes. Thus, variances, gas fluxes, Richardson number (above and inside the canopy), sensible heat, latent heat, turbulent kinetic energy, mean horizontal wind velocity and multiresolution decomposition were calculated. The main novelty of the present study was this analysis as a synthesis of the main methodologies used on the different scalar flows and their time scales within and above an Amazon rainforest canopy at the ATTO experimental site at night.